2021
DOI: 10.1016/j.onehlt.2020.100208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence of Coxiella burnetii in bulk-tank milk from bovine dairy herds: Systematic review and meta-analysis

Abstract: Coxiella burnetii is an obligate intracellular zoonotic bacterium that causes Q fever. Ruminants, including cattle, are broadly known to be reservoirs for this bacterium. Since 2006, many research groups have evaluated the herd-level prevalence of C. burnetii in cattle by molecular techniques on composite milk samples. This study explored the global C. burnetii herd-level prevalence from studies done on bovine bulk-tank milk (BTM) samples using PCR-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
(38 reference statements)
1
11
1
1
Order By: Relevance
“…2019; Basanisi et al, 2022). The global molecular prevalence of C. burnetii in milk samples has been estimated by meta-analysis (Rabaza et al, 2021). We carried out a comprehensive systematic review of the literature using keyword-based searches to determine the global molecular prevalence of C. burnetii in cheese samples.…”
Section: Discussionmentioning
confidence: 99%
“…2019; Basanisi et al, 2022). The global molecular prevalence of C. burnetii in milk samples has been estimated by meta-analysis (Rabaza et al, 2021). We carried out a comprehensive systematic review of the literature using keyword-based searches to determine the global molecular prevalence of C. burnetii in cheese samples.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 162 milk samples screened for C. burnetii using PCR, the bacteria was reported in 10.2% of goats, 18.6% in sheep, and 15% in cattle milk in Iran [47]. Furthermore, three studies conducted in Italian cattle herds in 2013 and 2014 also reported differences in C. burnetii prevalence of 40.0% and 60.0%, respectively [48]. All these observations point to the role of milk as a vehicle in the transmission of C. burnetii to humans.…”
Section: Coxiella Burnetii In Domestic and Peri-domestic Animalsmentioning
confidence: 99%
“…Em um estudo recente de meta-análise, foi demonstrado uma ampla circulação de C. burnetii em nível de rebanho em fazendas de gado leiteiro, com prevalência mundial de 37,0% em amostras de leite a granel, utilizando reação em cadeia da polimerase (PCR) (RABAZA et al, 2021).…”
Section: Epidemiologiaunclassified